Measuring Signal Generators Theory & Design - Rybin, Yuriy K.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
The book brings together the following issues: Theory of deterministic, random and discrete signals reproducible in oscillatory systems of generators; Generation of periodic signals with a specified spectrum, harmonic distortion factor and random signals with specified probability density function and spectral density; Synthesis of oscillatory system structures; Analysis of oscillatory systems with non-linear elements and oscillation amplitude stabilization systems; It considers the conditions and criteria of steady-state modes in signal generators on active four-pole elements with unidirectional and bidirectional transmission of signals and on two-pole elements; analogues of Barkhausen criteria; Optimization of oscillatory system structures by harmonic distortion level, minimization of a frequency error and set-up time of the steady state mode; Theory of construction of random signal generators; Construction of discrete and digital signal generators; Practical design of main units of generators; Practical block diagrams of both analog and digital signal generators.
Theory and Praxis of Measuring Signal Sources: Present and Future -- Synthesis of Mathematical Models for Measuring Signals -- Synthesis of Models for Self-Oscillating Systems of Generators -- Selected Issues of the Theory of Sinusoidal Generators -- Synthesis of Block Diagrams of Measuring Signal Generators -- Optimization of Oscillatory Systems of Generators -- Analog Signal Generators -- Digital Signal Generators -- Practical Design of Measuring Signal Generators.
Keywords: Engineering; Physical measurements; Measurement; Electronic circuits; Engineering; Signal, Image and Speech Processing; Measurement Science and Instrumentation; Circuits and Systems; Electronic books